Conflicting and Complementary Ethics of Animal Welfare Considerations in Reintroductions - Harrington, L; Moehrenschlager, A; Gelling, M; Atkinson, R; Hughes, J; Macdonald, D (2013)
Despite differences in focus, goals, and strategies between conservation biology and animal welfare, both are inextricably linked in many ways, and greater consideration of animal welfare, although important in its own right, also has considerable potential to contribute to conservation success. Nevertheless, animal welfare and animal ethics are not always considered explicitly within conservation practice. We systematically reviewed the recent scientific peer-reviewed and online gray literature on reintroductions of captive-bred and wild-caught animals (mammals, birds, amphibians, and reptiles) to quantify the occurrence of animal welfare issues. We considered monitoring that could be indicative of the animal's welfare status and supportive management actions that could improve animal welfare (regardless of whether the aim was explicitly animal-welfare orientated). Potential welfare issues (of variable nature and extent) were recorded in 67% of 199 projects reviewed; the most common were mortality >50%, dispersal or loss of animals, disease, and human conflict. Most (>70%) projects monitored survival, 18% assessed body condition, and 2% monitored stress levels. Animal welfare, explicitly, was referred to in 6% of projects. Supportive actions, most commonly use of on-site prerelease pens and provision of supplemental food or water, were implemented in 79% of projects, although the extent and duration of support varied. Practitioners can address animal-welfare issues in reintroductions by considering the potential implications for individual animals at all stages of the release process using the decision tree presented. We urge practitioners to report potential animal-welfare issues, describe mitigation actions, and evaluate their efficacy to facilitate transparent evaluation of common moral dilemmas and to advance communal strategies for dealing with them. Currently, comparative mortality rates, health risks, postrelease stress, effectiveness of supportive measures, and behavior of individuals warrant further research to improve animal welfare in reintroductions and to increase success of such projects. © 2013 Society for Conservation Biology.